Percutaneous peripheral nerve stimulation for the treatment of chronic neuropathic postamputation pain: a multicenter, randomized, placebo-controlled trial. Issue 6 (5th April 2019) - Gilmore, Christopher; Ilfeld, Brian; Rosenow, Joshua; Li, Sean; Desai, Mehul; Hunter, Corey; Rauck, Richard; Kapural, Leonardo; Nader, Antoun; Mak, John; Cohen, Steven; Crosby, Nathan; et al.
Abstract : Background and objectives: Chronic neuropathic pain is a common challenging condition following amputation. Recent research demonstrated the feasibility of percutaneously implanting fine-wire coiled peripheral nerve stimulation (PNS) leads in proximity to the sciatic and femoral nerves for postamputation pain. A multicenter, double-blinded, randomized, placebo-controlled study collected data on the safety and effectiveness of percutaneous PNS for chronic neuropathic pain following amputation. Methods: Twenty-eight lower extremity amputees with postamputation pain were enrolled. Subjects underwent ultrasound-guided implantation of percutaneous PNS leads and were randomized to receive PNS or placebo for 4 weeks. The placebo group then crossed over and all subjects received PNS for four additional weeks. The primary efficacy endpoint evaluated the proportion of subjects reporting ≥50% pain reduction during weeks 1–4. Results: A significantly greater proportion of subjects receiving PNS (n=7/12, 58%, p=0.037) demonstrated ≥50% reductions in average postamputation pain during weeks 1–4 compared with subjects receiving placebo (n=2/14, 14%). Two subjects were excluded from efficacy analysis due to eligibility changes. Significantly greater proportions of PNS subjects also reported ≥50% reductions in pain (n=8/12, 67%, p=0.014) and pain interference (n=8/10, 80%, p=0.003) after 8 weeks of therapy compared with subjects receiving placebo (pain: n=2/14, 14%; pain interference: n=2/13, 15%). Prospective follow-up is ongoing; four of five PNS subjects who have completed 12-month follow-up to date reported ≥50% pain relief. Conclusions: This work demonstrates that percutaneous PNS therapy may provide enduring clinically significant pain relief and improve disability in patients with chronic neuropathic postamputation pain. Trial registration number: NCT01996254 .